The Inclusion Paradigm in Greek schools: does just also mean justified? - Stergiadou, Aristi (Epistēmēs Metron Logos, 2022)
This article aims to clarify the term "inclusion" and to highlight its value within the school environment, as well as to promote inclusive education in Greece. First, an attempt is made to define the term followed by the presentation of the relevant legal framework. Next the differences between Special Education and Co-Education are pinpointed in order for the reader to identify their basic differentiating elements. Then the problems that hinder the implementation of inclusion in schools are presented and ways to solve them are suggested. Finally, the terms of “Inclusive” and “Intercultural Education” are analyzed and compared. Inclusion in Greece, despite the obstacles it faces, can become a dominant and constructive way of learning.